Інститут приватних детективів за кордоном: порівняльно-правовий аналіз - Бугайчук, К. Л.; Bugaychuk, K. L.; ResearcherID: I-5612-2016; Костянтин Бугайчук (Право і безпека. - 2016. - № 1 (60). - С. 7-13, 2016)
Проаналізовано особливості організації та діяльності приватних детективів у США та країнах Західної Європи. Досліджено основні права та обов’язки приватних детективів, вимоги до їх професійної підготовки, а також питання здійснення контролю за діяльністю приватних детективів. Окрему увагу приділено питанням взаємодії приватних детективів та органів поліції під час розслідування кримінальних справ та виявлення фактів вчинення кримінальних злочинів.

The features of organization and activities of private detectives in the US and Western Europe are analyzed. Basic rights and duties of private detectives, requirements for their training, as well as issues of control over their activities are investigated. Particular attention is paid to the interaction between private detectives and police in the investigation of criminal cases and detection of criminal offenses. Based on the study, following conclusions have been reached: activities of private detectives abroad are regulated by special legislation which divides the spheres of private detective activities and private security; for private investigators abroad qualifications for citizenship, education, training are required; there are special training courses for private detectives in colleges; private detectives cannot carry out certain procedural actions that fall into the purview of state law enforcement agencies: search, seizure, interrogation, use of special photo and video recording devices; private detectives can be granted access to the databases of the law enforcement agencies, enterprises, institutions.

Проанализированы особенности организации и деятельности частных детективов в США и странах Западной Европы. Исследованы основные права и обязанности частных детективов, требования к их профессиональной подготовке, а также вопросы осуществления контроля за деятельностью частных детективов. Отдельное внимание уделено вопросам взаимодействия частных детективов и органов полиции при расследовании уголовных дел и выявлении фактов совершения уголовных преступлений.
Institution of private detectives abroad: comparative and legal analysis
Институт частных детективов за границей: сравнительно-правовой анализ
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; приватний детектив; правоохоронна діяльність; розшук; поліція; США; країни Західної Європи; зарубіжний досвід; private detective; law enforcement; search; police; частный детектив; правоохранительная деятельность; розыск; полиция; зарубежный опыт; страны Западной Европы; USA; Western Europe